2019
DOI: 10.1029/2019jd031329
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Global Mean Eddy Diffusive Transport in the Mesosphere and Lower Thermosphere From Atomic Oxygen and Carbon Dioxide Climatologies

Abstract: Quantifying the eddy diffusion coefficient profile in the mesosphere and lower thermosphere (MLT) is critical to the constituent density distributions in the upper mesosphere and thermosphere. Previous work by Swenson et al. (2018, https://doi.org/10.1016/j.jastp.2018.05.014) estimated the global mean eddy diffusion (kzz) values in the upper mesosphere using atomic oxygen (O), derived from Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) hydroxyl (OH). In this study, vertical eddy diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 74 publications
1
20
0
Order By: Relevance
“…Several studies have reported the influence of gravity waves and turbulence on the T/I composition and calculated the eddy diffusion coefficient in the MLT region (Kirchhoff and Clemesha, 1983;Sasi and Vijayan, 2001;Swenson et al, 2019). Based on radar measurements, Kirchhoff and Clemesha (1983) calculated a minimum (maximum) eddy diffusion coefficient of 45 (123) m 2 s −1 during fall (summer).…”
mentioning
confidence: 99%
“…Several studies have reported the influence of gravity waves and turbulence on the T/I composition and calculated the eddy diffusion coefficient in the MLT region (Kirchhoff and Clemesha, 1983;Sasi and Vijayan, 2001;Swenson et al, 2019). Based on radar measurements, Kirchhoff and Clemesha (1983) calculated a minimum (maximum) eddy diffusion coefficient of 45 (123) m 2 s −1 during fall (summer).…”
mentioning
confidence: 99%
“…Ultimately it may be necessary to relax the assumptions of Equation . This coupled with using eddy diffusion values at the TIE‐GCM lower boundary such as those deduced from satellite observations (e.g., Salinas et al., 2016; Swenson et al., 2019) or possibly those from the TIME‐GCM at the TIE‐GCM lower boundary pressure level (e.g., Figure 1c, Jones Jr. et al., 2017) may be warranted to improve the amplitude of the global climatological T‐I SAO. This work is outside the scope of the current paper, but we note that the TIE‐GCM does not need to consider more oxygen chemistry than it already does.…”
Section: Resultsmentioning
confidence: 99%
“…Figure3balso indicates that the TSM does have some downward influence on MLT oxygen chemistry over large spatial and seasonal time scales, consistent with the underlying assumptions of 1D modeling work interested in describing the vertical transport and photochemistry of species in the MLT region (e.g.,Allen et al, 1981;Colegrove et al, 1966;Salinas et al, 2016;Swenson et al, 2019). We therefore JONES ET AL.…”
mentioning
confidence: 98%
“…(2014) demonstrated that the CO 2 distribution above ∼80 km depends sensitively on the effective eddy diffusion coefficient. Furthermore, the values from WACCM (∼5–50 m 2 /s between 80 and 100 km) are found to be smaller than those determined from observations (Swenson et al., 2019), and those required for achieving agreement with various measurements of constituents (Feng et al., 2013; Garcia et al., 2014; Orsolini et al., 2017; Randall et al., 2015; Smith‐Johnsen et al., 2018).…”
Section: Introductionmentioning
confidence: 84%
“…Salinas et al (2016) derived eddy diffusion from SABER CO 2 measurement, and it is ∼33 m 2 /s at 90 km. Swenson et al (2019) obtained global mean eddy diffusion coefficient from O determined by SABER OH measurements, with odd oxygen loss considered, and the value is 33-60 m 2 /s between 90 and 95 km. This is smaller than the eddy diffusion coefficient from an earlier estimate without considering the odd oxygen loss (Swenson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%